2010
DOI: 10.3800/pbr.5.214
|View full text |Cite
|
Sign up to set email alerts
|

Shell growth and reproductive cycle of the Mediterranean mussel Mytilus galloprovincialis in Tokyo Bay, Japan: relationship with environmental conditions

Abstract: This study investigates shell growth patterns and the reproductive cycle of the Mediterranean mussel Mytilus galloprovincialis in Tokyo Bay, central Japan. A follow-up study of marked mussels within the intertidal zone from July 2007 to September 2008 indicates a remarkably fast annual shell-growth rate and a short life span, reaching the maximum shell length (ca. 70 mm) at age 3 or 4 years. Histological examinations of mussel gonads collected fortnightly revealed that the Tokyo Bay population has a spawning s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
(34 reference statements)
1
19
0
Order By: Relevance
“…They observed that the number of growth increment formed during a limited interval of time is (sometimes significantly) lower than the number of days (or tides) at the study sites. Winter growth cessation is indeed common in bivalves (Jones and Quitmyer, 1996;Tanabe, 2007;Okaniwa et al, 2010), because the production of shell carbonate ceases below species-specific growth temperature thresholds. For instance, Margaritifera margaritifera in northern Sweden stops producing shell carbonate below 5 • C (Schöne, 2008) while M. galloprovincialis from Tokyo Bay, Japan, stops growing or barely grows for water temperature between 8 and 14 • C (Okaniwa et al, 2010).…”
Section: Periodicity In Shell Growth and Environmental Influencesmentioning
confidence: 99%
See 2 more Smart Citations
“…They observed that the number of growth increment formed during a limited interval of time is (sometimes significantly) lower than the number of days (or tides) at the study sites. Winter growth cessation is indeed common in bivalves (Jones and Quitmyer, 1996;Tanabe, 2007;Okaniwa et al, 2010), because the production of shell carbonate ceases below species-specific growth temperature thresholds. For instance, Margaritifera margaritifera in northern Sweden stops producing shell carbonate below 5 • C (Schöne, 2008) while M. galloprovincialis from Tokyo Bay, Japan, stops growing or barely grows for water temperature between 8 and 14 • C (Okaniwa et al, 2010).…”
Section: Periodicity In Shell Growth and Environmental Influencesmentioning
confidence: 99%
“…Winter growth cessation is indeed common in bivalves (Jones and Quitmyer, 1996;Tanabe, 2007;Okaniwa et al, 2010), because the production of shell carbonate ceases below species-specific growth temperature thresholds. For instance, Margaritifera margaritifera in northern Sweden stops producing shell carbonate below 5 • C (Schöne, 2008) while M. galloprovincialis from Tokyo Bay, Japan, stops growing or barely grows for water temperature between 8 and 14 • C (Okaniwa et al, 2010). Growth cessation may also occur all year round as a result of an abrupt change in the environmental conditions due to strong wind events, drop in salinity and/or phytoplankton bloom (due to toxicity or clogging of the gill system) (Page and Hubbard, 1987;Chauvaud et al, 1998;Schöne, 2008;Okaniwa et al, 2010).…”
Section: Periodicity In Shell Growth and Environmental Influencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing and success of reproduction is heavily weighed upon temperature and food availability (Sastry 1966;Suarez et al 2005;Lemaire et al 2006;Okaniwa et al 2010). For example, mussels (M. californianus) near the high edge of the mussel bed invested less energy into reproduction and spawned early in the summer compared to those in the lower edge, where food availability was high and reproduction occurred throughout the year (Petes et al 2008).…”
Section: Physiological Effectsmentioning
confidence: 99%
“…Previous studies identified several drivers that influence the shell growth rate of bivalves including temperature 5,6 , food supply and quality 7,8 , salinity 9 , latitude 1 and also reproduction 10 . Evidence for modification in growth in marine molluscs with the environment comes for example from the great scallop Pecten maximus along the Northeast Atlantic coast 1 and from the Mytilus edulis along the British coast in the Irish Sea 11 , showing a decrease in shell growth with higher temperatures.…”
Section: Introductionmentioning
confidence: 99%